+0  
 
0
97
2
avatar

When the expression\[1-1x+2x^2-2+3x-3x^2+4-4x+5x^2\]is written in the form $ax^2 +bx+c$, where $a$, $b$, and $c$ are non-zero integers, what is the value of $a + b + c$?

 Apr 9, 2021
 #1
avatar+2125 
+1

We need to combine like terms. 

(2x^2-3x^2+5x^2) + (-1x + 3x - 4x) + (1 - 2 + 4)

4x^2 - 2x + 3. 

 

4-2+3 = 5

 

I hope this helped. :))

 

=^._.^=

 Apr 9, 2021
 #2
avatar+121004 
+2

1 - 1x + 2x^2  - 2 + 3x -  3x^2  +  4  - 4x   + 5x^2     collect like terms

 

5x^2  - 3x^2 + 2x^2   - 4x + 3x  - 1x   +  4  -  2  +  1

 

4x^2   - 2x  +   3

 

a  =  4

b  = -2

c = 3

 

a + b +  c  =   4  - 2  + 3    =     5

 

 

cool cool cool

 Apr 9, 2021

14 Online Users

avatar